Memory disjunctivism: a causal theory - Moran, A (Springer, 2021)
Relationalists about episodic memory must endorse a disjunctivist theory of memory-experience according to which cases of genuine memory and cases of total confabulation involve distinct kinds of mental event with different natures. This paper is concerned with a pair of arguments against this view, which are analogues of the ‘causal argument’ and the ‘screening off argument’ that have been pressed in recent literature against relationalist (and hence disjunctivist) theories of perception. The central claim to be advanced is that to deal with these two arguments, memory disjunctivists both can and should draw on resources that are standardly appealed to by rival common factor theories of episodic memory, and, in particular, to the idea that genuine memories and merely apparent ones are to be distinguished, at least in part, in terms of the distinctive ways in which they are caused. On the proposed view, there are substantive causal constraints associated both with cases of genuine memory and with cases of mere confabulation. The resulting theory thus tells us something important about the nature both of genuine memories and of mere confabulations, namely, that such experiences must be caused in certain distinctive ways and cannot occur except as the result of a distinctive sort of causal process. In addition, the theory enables the disjunctivist to offer a unified response to an important pair of arguments against her view.